2020
DOI: 10.1021/jacs.0c10151
|View full text |Cite
|
Sign up to set email alerts
|

Electronically Coupled 2D Polymer/MoS2 Heterostructures

Abstract: Emergent quantum phenomena in electronically coupled two-dimensional heterostructures are central to nextgeneration optical, electronic, and quantum information applications. Tailoring electronic band gaps in coupled heterostructures would permit control of such phenomena and is the subject of significant research interest. Two-dimensional polymers (2DPs) offer a compelling route to tailored band structures through the selection of molecular constituents. However, despite the promise of synthetic flexibility a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 52 publications
1
36
0
Order By: Relevance
“…With few examples of patterned 2DPs for micrometer-scale devices, we first confirmed that the polymerized TIIP films formed and patterned as described above were comparable to those previously reported, [21] or those formed on isolated films on glass. The optically homogenous TIIP films polymerized by this method are of high quality, with strong preferentially oriented structural periodicity and a high degree of chemical purity.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…With few examples of patterned 2DPs for micrometer-scale devices, we first confirmed that the polymerized TIIP films formed and patterned as described above were comparable to those previously reported, [21] or those formed on isolated films on glass. The optically homogenous TIIP films polymerized by this method are of high quality, with strong preferentially oriented structural periodicity and a high degree of chemical purity.…”
Section: Resultssupporting
confidence: 86%
“…[21] Next, we explored polymerization conditions to obtain TIIP as a homogenous thin film. After optimization, we found that immersing a glass substrate into the solvothermal polymerization of TAPPy (5 × 10 −3 m, 1.0 equiv) and TII (10 × 10 −3 m, 2.0 equiv) in a mixture of o-dichlorobenzene:nbutanol:mesitylene:acetic acid:water (20:20:2:1:1 v/v/v) at 100 °C for 72 hours produced a crystalline, imine-linked 2DP films, as previously shown, [21] and confirmed below.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the surficial chemically inert pristine graphene, [47] 2D TMDs prepared through solution-based methods provide many chemical pathways for constructing functional heterostructures, [48][49][50] for example, TMD-based heterostructures can be covalently bonded with metal sites for improved catalytic activity and selectivity, [51] and electronically coupled with 2D polymer for enhanced photoluminescence. [52] 2D transition metal oxides (TMOs) with various chemical compositions and rich valence states is another common building block, which is primarily due to their relatively low costs and complex redox chemistry. [53][54][55][56][57] Besides the above-listed 2D materials, there are many other 2D basic building blocks that can be synthesized and modified for creating 2D/2D heterostructures, such as BP monolayer with an intrinsic direct bandgap of 1.5 eV, [58,59] LDHs with tuneable chemical compositions, [60] MXenes with a good conductivity and variable interlayer spacing, [61][62][63][64] graphene consisting of sp-and sp 2 hybridized carbon atoms, [65] and insulating h-BN with a graphite-like Two-dimensional/two-dimensional (2D/2D) heterostructures consisting of two or more 2D building blocks possess intriguing electronic features at the nanosized interfacial regions, endowing the possibility for effectively modulating the confinement, and transport of charge carriers, excitons, photons, phonons, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In molybdenum disulfide (MoS 2 ) monolay- ers (1L), strong spin-orbit coupling additionally 7 allows for direct control of the spin and valley degrees of freedom 3,8 and the possibility of exciting chiral phonons. 9,10 The coupling of monolayers in heterostructures, 11 moiré superlattices 12,13 or to underlying substrates 14 and modified dielectric environments 15 have opened further avenues for wide tunability in properties and control of correlated phases. Many effects in these (and other) 2D materials arise specifically from the interplay between electronic and vibrational degrees of freedom, known as electron-phonon coupling (EPC).…”
Section: Introductionmentioning
confidence: 99%